2022
DOI: 10.1002/jcla.24297
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutrition index is associated with the all‐cause mortality in sepsis patients: A retrospective cohort study

Abstract: Sepsis is caused by an aberrant regulatory host response toward an infection. It is linked to acute organ dysfunction and associated with high mortality. 1,2 Despite advances in care and treatment, sepsis remains the costliest disease to treat, with over $20 billion (5.2%) being spent annually in the United States. 3 The number of hospitalizations for sepsis cases in the United States even exceeds those for stroke and myocardial infarctions. 4 According to the statistics, 5 the incidence of sepsis is 500 per 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…As a combined biomarker of lymphocytes and albumin, PNI is simple, efficient, and easy to obtain [ 15 ]. In addition, PNI can reflect the severity of inflammation and the nutritional status of the disease at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a combined biomarker of lymphocytes and albumin, PNI is simple, efficient, and easy to obtain [ 15 ]. In addition, PNI can reflect the severity of inflammation and the nutritional status of the disease at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence showed that PNI was closely associated with clinical outcomes of cancer [ 13 , 14 ] and sepsis [ 15 , 16 ]. However, the prognostic role of PNI in the cases with stroke is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It could cause the deficiencies in some nutrients including minerals and vitamins, which also leads to the variations in RDW levels. 34 The strength of our research was that RDW could be a simple predictor for risk stratification of patients with septic shock based on large samples. Checking RDW on admission as early as possible and identifying its elevation as a risk factor of poor prognosis could be uti-…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, malnutrition may occur in some septic shock patients due to gastroenterological dysfunction. It could cause the deficiencies in some nutrients including minerals and vitamins, which also leads to the variations in RDW levels 34 …”
Section: Discussionmentioning
confidence: 99%
“…PNI was developed to assess the preoperative nutritional immune status and postoperative complications in surgical patients and has since been demonstrated to be a reliable prognostic factor for numerous malignancies, such as gastric cancer [ 16 ], intrahepatic cholangiocarcinoma [ 29 ], esophageal cancer [ 30 ], and nasopharyngeal carcinoma [ 31 ]. In the field of sepsis, Wu et al reported that after adjusting for confounding variables, PNI was asserted to be an independent prognostic factor for all-cause mortality at 30 days [ 32 ]. Additional studies have concluded that the presence and severity of neonatal sepsis were negatively and independently associated with PNI.…”
Section: Discussionmentioning
confidence: 99%